HUBUNGAN PENDIDIKAN, PENGETAHUAN DAN SIKAP SUAMI DALAM MENENTUKAN JENIS ALAT KONTRASEPSI - Kistijah Poltek Depkes Surakarta (Sekolah Tinggi Ilmu Kesehatan Estu Utomo Boyolali, 2009)
HUBUNGAN PENDIDIKAN, PENGETAHUAN DAN SIKAP SUAMI DALAM MENENTUKAN JENIS ALAT KONTRASEPSI KISTIJAH Poltekes Depkes Surakarta Abstrak Having reformation era now a days that appopriate human right and democration, so the emancipation between man and woman in some aspects of an absolute life must the accommodated. One of them is a decision which will be taken by the husband to choose contraceptive device. It will be used for husband of his wife to get a service in family planning. This research is a kind of survery research, with a research design of cross sectional. The target population of the research is a husband or man from fertile age couple. While, the population that can be reach in this research is a husband from fertile age couple in Pandes, Wedi, Klaten district on November in 2006. The purpose of the research is all of men who have wife and live in Pandes, Wedi, Klaten district. There are some inclusion qualifications juch as: a) man who has productif age wife; b) one of husband or wife become’s akseptor; c) live in Pandes, Wedi, Klaten district and; d) be willing to become respondent. The husband education didn’t affect husband decision in determining contrancentive device, c2: 0,008 (p>0,05). The husband knowledge affected the husband decision in determining contraceptive device, when c2: 6,782 (p< 0,05), OR: 6,513, CI 95%: 1,359-31,222. The husband attitude affected husband decision in determining the kind of contraceptive device, when c2: 18,913, (p< 0,05), OR: 13,958, CI 95%: 3,440-56,645. The research result proved that knowledge factor and husband attitude affected a husband decision in determining contraceptive device. Key word : The education stage, the knowledge, the attitude in family planning.